Quantitative Analysis and Antioxidant Activity of Polyphenolic Compounds in Whole Grain, Rice, and Bran of Hulless Barley - Junlin DENG; Chen XIA; Kaijun YANG; Tinghui LIU; Jian CHEN; Shigang XIE; Zhuoya XIANG; Xing YANG; Boyu ZHU; Manyou YU (Shipin gongye ke-ji)
This study focused on the extraction and analysis of β-glucan, free and bound phenols, total phenolic content (TPC), and total flavonoid content (TFC) from whole grain, rice, and bran of purple and glutinous hulless barley, and assessment of the antioxidant activity of extracts. Ultra-high-performance liquid chromatography (UPLC) quantified various phenolic compounds, including protocatechuic aicd, p-hydroxybenzoic acid, vanillic acid, caffeic acid, vanillin, p-coumaric acid, ferulic acid, sinspic acid, luteolin-7-O-glucuronide, chrysoeriol-7-O-glucuronide, luteolin, chrysoeriol, anthocyanin and 8 types of ferulic acid dimers. The antioxidant activities of free and bound phenolic extracts were evaluated by using DPPH and ABTS+ free radical scavenging assays. The results revealed that β-glucan content was comparable in whole grains and barley rice but significantly higher than that in bran (P<0.05). TPC and TFC were higher in bran than in whole grains or rice, with free phenolic extracts showing higher content than bound phenolic extracts. Bran contained a greater variety and higher content of bound polyphenols, followed by whole grains and rice. Particularly, ferulic acid was abundant in the bound phenolic extracts of bran of both barley types. The free phenolic extract of purple hulless barley bran showed high levels of chrysoeriol-7-O-glucuronic acid (1780.78 μg/g) and anthocyanins (2137.67 μg/g). Antioxidant assays demonstrated that hulless barley bran exhibited a stronger capability to scavenge DPPH and ABTS+ free radicals than whole grains and rice. This study provides a partial theoretical basis for the development and utilization of whole grain of hulless barley and hulless barley bran.